A PERSONAL VALUE APPROACH MODEL FOR ELEMENTARY LITERACY INSTRUCTION (World Bulletin of Social Sciences, 2023)
The worldview emerges as the context of the conceptual interpretation of the value relationship of the individual, the behavior as the norm, and the value relationship as the invariant to the system. In this way, the spiritual management of the knowledge of existence and the personal value approach is directed, and the content determines the behavior and attitudes of the individual. Therefore, education can be seen as a process of internalization of socially-organized universal values.